A educação física na escola indígena: limites e possibilidades - Albuquerque, Maria do Socorro Craveiro de (1999)
This work discusses a possible type of education that takes into account their particularities and interests. Specitically, it seeks to identify the limits and possibilities for the introduction of Physical Education in the indegenous curriculum. Firstly, I present a summary of the, main elements which determine the meaning and nature of the approach followed in treating the indegenous rights, and those one that drive the indians to face their perspectives for political actions. The firts one of those elements is related to population growth rate, that is higher than the national average; other elements are connected to the interference of economical interests, of the military, of the church and of the civil society, wich plays an important role in the struggle between the indians and non-indians in the national soiciety. In this respect, I also consider the articulations of the indigenous movement with other popular movements, a combination of various stregthens and ideas that give new meanings and directions to the defense of the Brazilian indians as legitimate members of the national multi-ethnic society. Next, I discuss the school education for indians from the perspective of the new concepts introduced in the decade of 1980, and the meaning of schooling as a reinforcement. The conclusions suggest that more efforts should be made the direcion of deseigning a Physical Education Program suitable to the indian in which the teachers should come from indian communities, and be prepared to do research on their own people's body languages. The research results could function as cultural revitalization, identify reinforcement, and also help in the appraisal of the body languages of the national society. These elements could possibly add to make the teaching/leaming context more relevant to the background and to the leaming process.